Double PIK3CA Alterations and Parallel Evolution in Colorectal Cancers. Issue 2 (14th September 2021) - Lin, Ming-Tseh; Zheng, Gang; Rodriguez, Erika; Tseng, Li-Hui; Parini, Vamsi; Xian, Rena; Zou, Ying; Gocke, Christopher D; Eshleman, James R
Abstract: Objectives: To demonstrate clinicopathologic features and evaluate the clonality of double PIK3CA alterations in colorectal cancers (CRCs). Methods: Clonality was examined in 13 CRCs with double PIK3CA alterations (1.7% of CRCs or 9.6% of PIK3CA -mutated CRCs). Multiregional analyses were performed to confirm subclonal PIK3CA alterations. Results: PIK3CA alterations were detected within exon 9 (51%), exon 20 (23%), exon 1 (15%), and exon 7 (6.0%). CRCs with exon 7 alterations showed a significantly higher incidence of double PIK3CA alterations. Most double PIK3CA alterations consisted of a hotpsot alteration and an uncommon alteration; they were often clonal and present within a single tumor population. Multiregional analyses of CRCs with predicted subclonal double-alterations revealed multiclonal CRCs with divergent PIK3CA variant status originating from a common APC - and KRAS -mutated founder lineage of adenoma. Conclusions: The findings supported multiclonal CRCs resulting from parallel evolution during the progression from adenoma to adenocarcinoma within the mitogen-activated protein kinase pathway, as previously demonstrated, or the mammalian target of rapamycin pathway. Further studies are warranted to elucidate clinical significance and potential targeted therapy for CRC patients with double PIK3CA alterations and impacts on clinical decision-making in patients with multiclonal CRCs harboring divergent PIK3CA mutational status.